Prospective study of determinants and costs of home births in Mumbai slums - Das Sushmita; Bapat Ujwala; More Neena; Chordhekar Latika; Joshi Wasundhara; Osrin David (BMC, 2010)
Abstract Background Around 86% of births in Mumbai, India, occur in healthcare institutions, but this aggregate figure hides substantial variation and little is known about urban home births. We aimed to explore factors influencing the choice of home delivery, care practices and costs, and to identify characteristics of women, households and the environment which might increase the likelihood of home birth. Methods As part of the City Initiative for Newborn Health, we used a key informant surveillance system to identify births prospectively in 48 slum communities in six wards of Mumbai, covering a population of 280 000. Births and outcomes were documented prospectively by local women and mothers were interviewed in detail at six weeks after delivery. We examined the prevalence of home births and their associations with potential determinants using regression models. Results We described 1708 (16%) home deliveries among 10 754 births over two years, 2005-2007. The proportion varied from 6% to 24%, depending on area. The most commonly cited reasons for home birth were custom and lack of time to reach a healthcare facility during labour. Seventy percent of home deliveries were assisted by a traditional birth attendant (dai), and 6% by skilled health personnel. The median cost of a home delivery was US$ 21, of institutional delivery in the public sector US$ 32, and in the private sector US$ 118. In an adjusted multivariable regression model, the odds of home delivery increased with illiteracy, parity, socioeconomic poverty, poorer housing, lack of water supply, population transience, and hazardous location. Conclusions We estimate 32 000 annual home births to residents of Mumbai's slums. These are unevenly distributed and cluster with other markers of vulnerability. Since cost does not appear to be a dominant disincentive to institutional delivery, efforts are needed to improve the client experience at public sector institutions. It might also be productive to concentrate on intensive outreach in vulnerable areas by community-based health workers, who could play a greater part in helping women plan their deliveries and making sure that they get help in time.